Describe The Opinion of Midwives on The Participation of Father/Family as Humanization Strategy of Care During Labor of Women Cared for at Clinic Vera Cruz, Dili, Timor-Leste - Jose Tilman, Etelvina; Monteiro, Ermelinda; Pereira, Natalia; de Deus, Elisa; de Carvalho, Eugenia; Dionisio Ximenes, Jose (Rifa'Institute, 2023)
Introduction: According to the World Health Organization (WHO, 2005) a normal delivery is the process in which labor begins spontaneously (the birth canal) with a low-risk index at the beginning of the work and cephalic presentation, a pregnancy between 37-42 weeks. After birth mother and baby remain in good condition. Objectives: To describe the opinion of midwives on the participation of father / family as humanization strategy of care during labor of women cared for at Clinica Vera Cruz, Dili, Timor-Leste. This is an exploratory and descriptive study with a qualitative approach, using semi structured interviews. Method: The total number of this health center midwives is 17. The sample consisted of the midwives who perform functions in maternal and fetal health to mothers. Results and Discussion: All midwives consider important the father attend the birth, favoring humanized care to women in labor, lessens the trauma of childbirth and the use of medicalization. The involvement of the father in childbirth contributes to their psychoactive preparation for better recovery of women, promotes the involvement of the couple in promoting the health of the mother and baby. Humanized births are quicker and develop more naturally. Conclusion: This research is beneficial to the women and for caregivers responsible for decision-making in the health center of Vera Cruz, especially midwives. The involvement of the father in normal birth is consensus as great benefit to the tirade (father, child & mother) with many advantages for the provision of humanized maternal and child care and to humanize the time of delivery and reduce the trauma and the hospital stay associated with it.